2012
DOI: 10.1128/aac.05701-11
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Confirming Data on the In Vivo Efficacy of Novel Antibacterial Drug Regimens against Various Strains of Mycobacterium tuberculosis

Abstract: In preclinical testing of antituberculosis drugs, laboratory-adapted strains of Mycobacterium tuberculosis are usually used both for in vitro and in vivo studies. However, it is unknown whether the heterogeneity of M. tuberculosis stocks used by various laboratories can result in different outcomes in tests of antituberculosis drug regimens in animal infection models. In head-to-head studies, we investigated whether bactericidal efficacy results in BALB/c mice infected by inhalation with the laboratory-adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
(54 reference statements)
5
32
1
Order By: Relevance
“…The results revealed that for the Beijing genotype bacteria, a much higher dosage of rifampin was required to achieve 100% killing, and two out of five Beijing strains exhibited a remarkably high frequency of mutations conferring rifampin resistance (7). These data underline the importance of the use of different M. tuberculosis strains in preclinical experimental studies using animal models, as stated by de Groote et al (3). They recommend the use of different M. tuberculosis strains in the confirmation of treatment efficacy results of novel drugs in the translational phase in order to strengthen the likelihood of success of novel drug regimens that advance into clinical trials (3).…”
mentioning
confidence: 85%
“…The results revealed that for the Beijing genotype bacteria, a much higher dosage of rifampin was required to achieve 100% killing, and two out of five Beijing strains exhibited a remarkably high frequency of mutations conferring rifampin resistance (7). These data underline the importance of the use of different M. tuberculosis strains in preclinical experimental studies using animal models, as stated by de Groote et al (3). They recommend the use of different M. tuberculosis strains in the confirmation of treatment efficacy results of novel drugs in the translational phase in order to strengthen the likelihood of success of novel drug regimens that advance into clinical trials (3).…”
mentioning
confidence: 85%
“…Efforts to confirm these promising results in a second animal model and against a second strain of M. tuberculosis are warranted (9). The second model could include another mouse strain (e.g., C3HeB/ FeJ mice), guinea pigs, or larger species, which all exhibit more human-like pathology (2,7,15), or the intravenous inoculation mouse model, which is known to produce more conservative estimates of treatment durations needed to prevent relapse (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…To control for this factor in a systematic manner, well-characterized reference collections encompassing representatives of all major MTBC genotypes and species must be tested in vitro and in vivo, given that even the differences among the various stocks of the H37Rv laboratory strains can be significant (38,89). The identity of the clinical isolates in these collections should be confirmed using multiple deletions or single-nucleotide polymorphisms rather than traditional techniques to avoid the pitfalls of homoplasy (1, 36, 52, 62, 84, 109, 135, 142).…”
Section: New Standards For Future Studiesmentioning
confidence: 99%